2006
DOI: 10.1128/aem.72.5.3637-3645.2006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Biochemical Characterization of Two Novel Metagenome-Derived Esterases

Abstract: The metagenomes of uncultured microbial communities are rich sources for novel biocatalysts. In this study, esterase EstA3 was derived from a drinking water metagenome, and esterase EstCE1 was derived from a soil metagenome. Both esterases are approximately 380 amino acids in size and show similarity to ␤-lactamases, indicating that they belong to family VIII of the lipases/esterases. EstA3 had a temperature optimum at 50°C and a pH optimum at pH 9.0. It was remarkably active and very stable in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
121
1
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 52 publications
7
121
1
14
Order By: Relevance
“…This clearly differentiates them from bona fide β-lactamases. EstU1, on the other hand, cleaves the amide bond of first generation β-lactam antibiotics, although it is more efficient at hydrolysing short chain esters [48]. Other family VIII esterases (EstM-N1, EstM-N2, EstC) have demonstrated activity on nitrocefin, although it is not clear from the data presented whether this constitutes deacetylation or amide bond hydrolysis [18,37].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This clearly differentiates them from bona fide β-lactamases. EstU1, on the other hand, cleaves the amide bond of first generation β-lactam antibiotics, although it is more efficient at hydrolysing short chain esters [48]. Other family VIII esterases (EstM-N1, EstM-N2, EstC) have demonstrated activity on nitrocefin, although it is not clear from the data presented whether this constitutes deacetylation or amide bond hydrolysis [18,37].…”
Section: Discussionmentioning
confidence: 48%
“…As a result, family VIII esterases are typically tested for their ability to hydrolyse a variety of β-lactam substrates ( Table 2). The majority either lack the activity or show negligible activity, despite the high sequence identity to the β-lactamases, while others have been described as exhibiting "promiscuous β-lactamase activity" [18,21,41,47,48,49]. Consequently, it has been suggested that these esterases have evolved from the class C β-lactamases, where some have maintained this remnant activity, while others have lost the capability due to steric interference resulting from structural evolution [18,41,50].…”
Section: Discussionmentioning
confidence: 99%
“…Recent examples include those preferably hydrolyzing one of the chiral esters in racemic mixtures of ibuprofen esters [9,10]; ketoprofen esters [11][12][13][14]; solketal esters [15]; esters of phenylalkyl carboxylic acids, 1,1,1-trifluoro-2-phenylbut-3-yn-2-yl acetate and 3,7-dimethyl-1,6-octadien-3-yl acetate [16,17]; methyl 3-phenylglycidate [18]; 1-phenylethyl acetate [19,20]; ofloxacin butyl ester [21]; 1-octin-3-ol, 3-chlor-1-phenyl-1-propanol, trimethylsilylbutinol, cis/trans-1,2-cyclohexanediol, and isopropylidenglycerol acetate [22]; glycidyl butyrate [23]; methyl-mandelate, glycidyl-4-nitrobenzoate, methyl-3-bromo-2-methyl propionate, methyl lactate, menthyl acetate, neomenthyl acetate, pantolactone, and methyl 3-hydroxybutyrate [22,24,25]; 1-octin-3-ol, 3-chlor-1-phenyl-1-propanol, and trimethylsilylbutinol [22]; methyl-3-hydroxy-2-methylpropionate [26]; and esters of secondary alcohols [27,28], to cite some. The advances in metagenomics techniques and screening methods have allowed the discovery of these and other selective esterases [29].…”
Section: Introductionmentioning
confidence: 99%
“…Demand for novel biocatalysts is continuously increased and thereby prompting the development of novel experimental approaches to find and identify novel biocatalyst-encoding genes. Recently, there has been an increase in the number of studies using a metagenomics approach to investigate the catalytic potential of uncultured microorganisms [2].…”
Section: Introductionmentioning
confidence: 99%